Advancing Pediatric Robotic Colorectal Surgery: Trends, Outcomes, and Future Directions—A Comprehensive Review - Pini Prato, Alessio; Lacher, Martin (European Journal of Pediatric Surgery, 2025)
Introduction Pediatric robotic colorectal surgery has rapidly evolved, offering enhanced precision and safety for treating complex conditions such as Hirschsprung disease (HSCR), anorectal malformations (ARMs), and inflammatory bowel disease (IBD). This review analyzes recent trends, outcomes, and complications in robotic colorectal procedures for pediatric patients.Materials and Methods A systematic review was performed using PubMed, yielding 1,112 articles related to pediatric robotic colorectal surgery. After applying exclusion criteria, 35 papers were analyzed, focusing on patient characteristics, procedure types, and clinical outcomes.Results Since 2001, approximately 700 pediatric patients have undergone robotic colorectal procedures, with HSCR being the most commonly treated condition (n = 421). The review highlights that 1.7% of patients experienced Clavien–Dindo grade III complications, while 11.5% had grade I to II complications, indicating a favorable safety profile. The use of robotic platforms facilitated improved precision during perirectal dissection and reduced the risk of damage to adjacent structures, particularly in cases requiring complex pelvic dissections. Despite promising outcomes, the uptake of robotic colorectal surgery remains lower than that for urologic procedures due to challenges such as cost, instrument size, and specialized training.Conclusion Robotic colorectal surgery in children is a safe and effective approach, particularly for complex conditions like HSCR, IBDs, and ARMs. While adoption is currently limited by cost and training requirements, ongoing advancements in technology and techniques promise to broaden its application and improve outcomes in pediatric surgery.
Keywords: pediatric robotic surgery; colorectal surgery; hirschsprung disease; anorectal malformations; inflammatory bowel diseases